PEMANFAATAN BLOG SEBAGAI MEDIA PEMBELAJARAN (Jurnal TEKNODIK, 2018)
The use blog as a learning media has not been done optimally by the teacher. This is because many teachers do not understand how and what steps must be taken in utilizing blog as learning media. The use blog as learning medai can be done at all levels, either elementary (SD), junior high (SMP), high school (SMA) or vocational school (SMK), because students in general are accustomed to accessing information through the web. But in this paper the use of blogs is more focused on junior and senior high school/vocational level, because the blog creation planning accompanied by the steps to prepare an online quiz that will be embedded into the blog. This is done as one effort to prepare students facing UNBK. This study was conducted in LPMP Bengkulu from January to March 2018. In this paper described the steps in the utilization of blogs as a learning media. This study begins by studying various literature and similar study results, to get a picture related to the use of blogs as a learning media. After this study, information was obtained that various problems in schools related to learning media could be overcome by utilizing blogs as learning media. In the future, it is expected that teachers can use blog as a learning media so that they can attract more interest and attention of the students.Pemanfaatan blog sebagai media pembelajaran belum dilakukan guru secara optimal. Hal ini disebabkan karena banyak guru belum memahami bagaimana dan langkah apa yang harus ditempuh dalam memanfaatkan blog sebagai media pembelajaran. Pemanfaatan blog sebagai media pembelajaran dapat dilakukan pada semua jenjang baik SD, SMP, SMA maupun SMK karena peserta didik secara umum sudah terbiasa mengakses informasi melalui web. Namun di dalam tulisan ini, pemanfaatan blog lebih difokuskan pada satuan pendidikan SMP dan SMA/SMK karena perencanaan pembuatan blog disertai dengan langkah penyiapkan kuis online yang akan disematkan ke blog. Hal ini dilakukan sebagai salah satu usaha menyiapkan peserta didik menghadapi UNBK. Kajian ini dllakukan di LPMP Bengkulu pada bulan Januari s.d Maret 2018. Dalam tulisan ini, dijabarkan langkah-langkah dalam pemanfaatan blog sebagai media pembelajaran. Kajian ini diawali dengan mempelajari berbagai literatur dan hasil kajian sejenis untuk mendapatkan gambaran terkait pemanfaatan blog sebagai media pembelajaran. Setelah dilakukan kajian ini maka diperoleh informasi bahwa berbagai permasalahan di sekolah terkait media pembelajaran dapat diatasi dengan memanfaatkan blog sebagai media pembelajaran. Kedepan diharapkan guru-guru dapat memanfaatkan blog sebagai media pembelajaran sehingga dapat lebih menarik minat dan perhatian para peserta didik.
Keywords: Learning media; blog usage; information access